(untitled) (Journal of the College of Languages (JCL), 2017)
מטרת המחקר הזה היא לבדוק את שלושה סיפורים קצרים מהקובץ הראשון של אהרון אפלפלד , שנחשב ההצהרה הרשמית על היותו סופר השואה הראשון בישראל , המשותף לשלושת הסיפורים הוא הנימה של הגיבורים היוצאים למסע פיזי ונפשי לגלות את אשר אירע להם , מגמתו של המחקר היא לבדוק את הצורה המיוחדת שבה אפיין אפלפלד את גיבוריו שמעידים על כך , כי השואה היא החוויה המרה והקשה בקרב היהודים והשלכותיה נשארה טמונה בקרבם גם אחרי המלחמה ואחרי שנים רבות. בהצגת שלושה הסיפורים נראה כי גיבוריו של אפלפלד , במודע או שלא במודע שקועים בים החרדה שנובעת מתקופת השואה והיא ממשיכה עמם , לכן הם נקרעו לשניים חרדה מפני העתיד המעורפל הבא , וחייהם השברירים המרוסקים בהווה , עם חרדה נובעה מן טראומות העבר הקשה לשכוח. Abstract This research(The Holocaust and its impact on Aharon Bielefeld - A Study in Three Short Stories) aims to shed light on three short stories from the collection of short stories first Writer (Aharon Appelfeld), which is the official announcement about being Writer of the Holocaust, the first in Israel, and share these stories tone characters who are engaged in physical, emotional conflict in the matter of figuring out what happened to them, as well as Find touches to distinctive way who painted him Appelfeld his characters, which indicate that the Holocaust was a bitter and difficult experience passed on the implications of the Jews remained subdued in their hearts even after the war and after so many years. It appears from the presentation of these stories, the characters are immersed consciously or unconsciously in a sea of ​​anxiety caused by the Holocaust, which remained its impact continues with them, so they turn in two halves, worry taint mysterious and shattered lives and devastating the future at the moment, the fear stems from the traumas of the past difficult Forgetting.